Why are you afraid of Indians: Issues of representation and misrepresentation in (Portuguese) children's literature - Amante, Susana (International Journal of Arts and Sciences - UniversityPublications.net, 2014)
Who hasn’t heard the phrase: “You look like an Indian”, to express that one is being naughty, or lazy, or violent or. something else, as long as it is negative? I have heard it a lot as a child and even nowadays, as a mother myself, I see/listen to (mis)representations when it comes to referring to First Nations – or indigenous peoples, if you will. In fact, before embarking on my research in Native Canadian literature for children and young adults and especially when I was about to depart to Canada to visit a reserve in Penticton and in Vernon, everyone around me took interest in what I was doing and told me I was crazy, as this seemed to be a dangerous field. In Portugal, songs and books for children still convey the image of the Indian as a merciless warrior who is ready to scalp you and peel your skin off. That is the reason why, after studying Native Canadian literature for children and young adults, I believe it is important to analyse the way that the Indian is still portrayed in Portuguese literature, in particular through a brief reading and discussion of Maria Teresa Maia Gonzalez’s A História dos Brincos de Penas, a book that is recommended by the Portuguese National Reading Panel. Thus, this study combines postcolonial theory and literary criticism to discuss issues of representation and misrepresentation, ultimately leading us to understand the importance of Bhabha’s third space, a space where positive negotiations and renegotiations give rise to hybridity, a space where one does no longer need to be afraid of Indians. FCT and CI&DETS (Pest-OE/CED/UI4016/2011)